Pediatric lung transplant: Correlation of pretransplant condition with post‐transplant outcomes. (28th October 2020) - Freiberger, Dawn; Gould Delaney, Anne; Forbes, Peter; Manley, Donna; Visner, Gary A.
Abstract: Background: It is generally accepted that patients who have greater functional capacity are better candidates for lung transplantation. Accurate assessment of physical condition is important in identifying appropriate candidates for transplant. The focus of this study was to determine which measures of pretransplant physical condition correlate with positive post‐transplant outcomes in children undergoing lung transplant. Methods: A retrospective chart review was done on 44 patients, ages 5 to 21 years. The pretransplant data collected included functional status, 6MWT, ambulatory status, and mechanical support. Post‐transplant outcome data included time on the ventilator, days in the ICU, length of hospitalization, and 12‐month survival. Results: Results were analyzed using Fisher exact and Kruskal‐Wallis tests. Patients with limited ambulation had more days in the ICU compared to the most ambulatory group ( P  = .043). Patients independent or needing some help with ADL had less time on the ventilator compared to patients needing total help. ( P  = .014). Patients with 6MWT result greater than 500' had fewer ICU days ( P  = .044) and marginally better 12‐month survival ( P  = .057). The 12‐month survival of children needing invasive ventilatory support pretransplant was not significantly worse than those who did not; however, they required significantly more time on the ventilator ( P  = .004), days in ICU ( P  = .013), and longer hospitalization. Discussion: This study demonstrated that pretransplant physical condition affects post‐transplant outcomes in children. Measures associated with positive post‐transplant outcomes were identified and could be beneficial in determining which patients are optimal candidates for lung transplant.